2022
DOI: 10.1037/ort0000586
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic discrimination, social cohesion, and mental health among Latinx adults.

Abstract: The negative effects of ethnic discrimination on depression symptoms have led researchers to identify potential risk and protective variables of this relationship. While some studies have focused on individual level factors, little research has explored the role of community-level variables, or the combination of both. The present study of Latinx adults (N = 304) tested a moderated mediation model to examine if alcohol use was a mediator of ethnic discrimination and depression under certain levels of social co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For example, several men spoke about the protective effect of embracing the cultural significance of social connection through family interactions and positive interpersonal interactions, which influenced their own agency in helping others, and the benefits of increased community support on their health. Literature has identified discrimination and social exclusion as a risk factor that impacts the well-being and health of Latinxs (e.g., LeBrón & Viruell-Fuentes, 2020; Martínez et al, 2022; Torres et al, 2022) and identified social support as protective against discrimination experiences (e.g., Bostean et al, 2019; Garcini et al, 2020; Lee et al, 2020; Organista & Ngo, 2019). Our findings expand on this literature by identifying familismo , simpatía , and community support as protective factors that are culturally relevant to PR men and help buffer against the discrimination they face.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several men spoke about the protective effect of embracing the cultural significance of social connection through family interactions and positive interpersonal interactions, which influenced their own agency in helping others, and the benefits of increased community support on their health. Literature has identified discrimination and social exclusion as a risk factor that impacts the well-being and health of Latinxs (e.g., LeBrón & Viruell-Fuentes, 2020; Martínez et al, 2022; Torres et al, 2022) and identified social support as protective against discrimination experiences (e.g., Bostean et al, 2019; Garcini et al, 2020; Lee et al, 2020; Organista & Ngo, 2019). Our findings expand on this literature by identifying familismo , simpatía , and community support as protective factors that are culturally relevant to PR men and help buffer against the discrimination they face.…”
Section: Discussionmentioning
confidence: 99%
“…The current study attempts to address several gaps in the existing research literature. Although the exploration of these constructs is increasing in frequency (Torres et al 2022), limited work tests social cohesion as a mediator of discrimination-health associations. Therefore, this study tested a mediation model among LGBT individuals in Chicago, in which self-reported discrimination experiences were proposed to inversely relate to four self-reported health domains (e.g., general health, healthcare access, mental health, and physical health); social cohesion was proposed to relate positively to health; and the discrimination-health associations were proposed to be mediated by perceived feelings of social cohesion (See Figure 1).…”
Section: Present Studymentioning
confidence: 99%